2017
DOI: 10.1177/1938965517719267
|View full text |Cite|
|
Sign up to set email alerts
|

Progress in Research on CSR and the Hotel Industry (2006-2015)

Abstract: This study reviews and synthesizes the contemporary literature focusing on the role of corporate social responsibility (CSR) in the hotel industry over the period 2006-2015. The revision process has covered articles meeting two conditions: first, articles focusing exclusively on the hotel industry (not on the tourism sector as a whole) and, second, the issue of CSR is addressed from a broader perspective (economic-social-environmental) and not only environmental. A total of 48 papers have been identified and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
137
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(161 citation statements)
references
References 71 publications
3
137
0
12
Order By: Relevance
“…Much of the existing research evaluates the impacts of CSR on organizational outcomes (Jones, Willness, & Madey, 2014). More research is being conducted that examines CSR's contribution to firms' competitive advantage and long-term performance in hospitality, including environmental and community benefits (Levy & Park, 2011;Gu, Ryan, Li, & Wei, 2013;Tsai, Hsu, Chen, Lin, & Chen , 2010), reputation, customer satisfaction and loyalty (Font, Walmsley, Cogotti, McCombes, & Häusler, 2012;Gao & Mattila, 2014;Levy & Park, 2011; Martinez & Bosque, 2013), business performance (Aminudin, 2013;Calveras, 2015;Kujawski, 2015 ;McGehee, Wattanakamolchai, Perdue, & Calvert, 2009;Serra-Cantallops et al, 2017;Zhu, Sun, & Leung, 2014). Besides the impacts on organizations, the effects of CSR on individual employee outcomes are thought also to be significant (Aguinis & Glavas, 2012).…”
Section: Csr and Organizational Identificationmentioning
confidence: 99%
See 3 more Smart Citations
“…Much of the existing research evaluates the impacts of CSR on organizational outcomes (Jones, Willness, & Madey, 2014). More research is being conducted that examines CSR's contribution to firms' competitive advantage and long-term performance in hospitality, including environmental and community benefits (Levy & Park, 2011;Gu, Ryan, Li, & Wei, 2013;Tsai, Hsu, Chen, Lin, & Chen , 2010), reputation, customer satisfaction and loyalty (Font, Walmsley, Cogotti, McCombes, & Häusler, 2012;Gao & Mattila, 2014;Levy & Park, 2011; Martinez & Bosque, 2013), business performance (Aminudin, 2013;Calveras, 2015;Kujawski, 2015 ;McGehee, Wattanakamolchai, Perdue, & Calvert, 2009;Serra-Cantallops et al, 2017;Zhu, Sun, & Leung, 2014). Besides the impacts on organizations, the effects of CSR on individual employee outcomes are thought also to be significant (Aguinis & Glavas, 2012).…”
Section: Csr and Organizational Identificationmentioning
confidence: 99%
“…Hospitality firms should practice CSR to protect the environment and show concern for the well-being of communities to support the sustainable development of the economy, society, and environment (Nyahunzvi, 2013). Considerable evidence indicates that CSR has a positive impact on hotel competitive advantage (Farrington et al, 2017;Luo & Bhattacharya, 2006;Serra-Cantallops, Peña-Miranda, Ramón-Cardona, & Martorell-Cunill, 2017;Su, Swanson, Hsu, & Chen, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The interpretation of positive and negative effects reflects how hotel general managers, hotel financial managers, and food and beverage managers perceive the drivers and boundaries of the adoption of ISO26000 and information provided on the Egyptian hotels ( Figure 1). The mediator factor ISO adoption showed a significant positive effect on hotel performance approved with (Lindgreen et al, 2018), ISO adoption has a significant positive effect on market share agreed with (Serra-Cantallops et al, 2018), ISO adoption has a significant positive effect on competitive advantages accepted with (Moyeen et al, 2019), and ISO adoption has a significant positive effect on reputation shown with (Lindgreen et al, 2018).…”
Section: 731 Agreementioning
confidence: 97%